Sagnac-interferometer-based multiwavelength SOA fiber laser assisted by an intensity-dependent loss mechanism - Sulaiman A.H.; David A.P.; Ismail A.; Abu Hassan N.N.; Abdullah F.; Jamaludin M.Z.; Yusoff N.M. (Optica Publishing Group (formerly OSA), 2025)
We demonstrate a Sagnac-interferometer-based multiwavelength fiber laser with an intensity-dependent loss (IDL) mechanism in the L-band region using a semiconductor optical amplifier (SOA) as the gain medium. The IDL mechanism flattens and stabilizes the multiwavelength spectrum. We also investigate the effect of rotation angles of polarization controllers (PCs) at different polarization devices on multiwavelength performance. At best settings, 31 lasing lines within 3 dB uniformity were generated with an extinction ratio (ER) of 17 dB. Adjusting the half-wave plate of PC1 and PC2 from 0? to 90? shifted the multiwavelength output by 0.01 nm and 0.072 nm, respectively. PC2 adjustment also affects the multiwavelength flatness as compared to PC1. Furthermore, the number of lasing lines and the ER were directly influenced by the SOA current. ? 2024 Optica Publishing Group.